EFEKTIVITAS PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DALAM PENERAPAN MODEL INCREMENTAL UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA (SMP) - Yanti Azmaniar; Mega Mustika Ali; Sufyarma M; Irsyad Irsyad (STKIP Pesisir Selatan, 2025)
This study is a literature review that examines the effectiveness of school principals' decision-making when applying the incremental model to improve the quality of education at the junior high school level. The incremental model—rooted in the tradition of public policy theory (Lindblom)—suggests gradual change and small improvements (‘muddling through’) as a managerial strategy when information is limited and uncertainty is high. This article summarises empirical evidence and theoretical studies (2015–2025) on: (1) the characteristics of school principals' decision-making; (2) the advantages and limitations of applying an incremental approach in schools; (3) the relationship between decision-making styles and education quality indicators (learning outcomes, school climate, resource management); and (4) policy and practice implications for principal capacity development. The results of the study show that the incremental approach is often effective in the context of complex and risky school operations if major changes are implemented without support; however, its effectiveness depends on the capabilities of the headteacher (managerial and leadership competencies), stakeholder participation, and clear monitoring and evaluation mechanisms.